CORC-like cable production and characterization of the solenoid made from it. (1st February 2019) - Šouc, J; Gömöry, F; Solovyov, M; Vojenčiak, M; Kujovič, T; Seiler, E; Kováč, J; Frolek, L; Behúlová, M; Janovec, J; Cuninková, E; Mišík, J; et al.
Abstract: A new cabling machine was constructed for conductor on round core (CORC)-like cable production. Its design allowed us to produce a cable with two layers in one run, each comprising four superconducting tapes. The cable of length of 40 m was made at a production rate of 6 m h −1 by this machine. It consisted of eight Furukawa-SuperPower tapes of width 4 mm and length 50 m wound in two layers on Cu tube with outer diameter 6.35 mm. To detect the influence of the cable winding technology on the superconducting tapes' properties their critical currents were measured individually on the as-produced cable in the form of a one-layer coil. Afterwards the critical current of the one-layer coil was measured by monitoring the voltages on all tapes while increasing the coil current. The average of these voltages was utilized for coil critical current determination. Then the solenoid with four layers each containing 20 turns was created from the cable and the same measurement procedure was performed to check the influence of cable bending on the solenoid form. The results of these characterizations exclude critical current degradation for any tape of the cable used for solenoid preparation. The measured solenoid critical current of 622.8 A is lower than the simple sum 1240 A of the individual tapes' critical currents due to the dependence of the tape critical current on the magnetic field. For all measurements the investigated object was immersed into a liquid nitrogen bath. In the case of the solenoid the bath was also cooled down to 66 K.